2022
DOI: 10.1111/cup.14217
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytic matricoma: A report of three cases, review of the literature, and suggestion of a new terminology

Abstract: Melanocytic matricoma is a rare, biphasic adnexal tumor. It typically presents as a pigmented papule on the sun‐damaged skin of elderly patients. Histopathology shows a dermal nodule composed of basaloid cells, ghost cells, and deeply pigmented dendritic melanocytes. The basaloid cells are usually positive for β‐catenin and these tumors show overlapping histopathological and molecular features with pilomatricoma. Here, we review the literature on melanocytic matricoma and present three new cases. We suggest di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Melanocytic matricoma typically presents as a small darkly pigmented papule on sun-damaged skin of elderly male patients. 3 Presentation on females appears to be significantly less common. 4 The clinical differential diagnosis includes pigmented pilomatricoma, basal cell carcinoma with matrical differentiation, pigmented trichoblastoma.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Melanocytic matricoma typically presents as a small darkly pigmented papule on sun-damaged skin of elderly male patients. 3 Presentation on females appears to be significantly less common. 4 The clinical differential diagnosis includes pigmented pilomatricoma, basal cell carcinoma with matrical differentiation, pigmented trichoblastoma.…”
Section: Discussionmentioning
confidence: 97%
“…These cases contribute to the literature as they reinforce the clinical presentation of melanocytic matricoma, with both cases presenting as small, pigmented papules on sun damaged skin of elderly men. 3 …”
Section: Discussionmentioning
confidence: 99%
“…In the existing literature, there has been some controversy regarding the proper characterization of this tumor. Some have suggested that melanocytic matricomas are either a subtype of pilomatricoma or exist on a spectrum, including pilomatricomas [1,5].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor contains basaloid cells (round nuclei, stippled chromatin, prominent nucleoli) that transition into shadow (ghost) cells (anucleate, eosinophilic, keratinized cytoplasm) in a manner that can be either abrupt or gradual [1]. The tumor also contains melanocytes, which are usually intermixed among the other components of the tumor [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation